The Role of Macrophage Migration Inhibitory Factor in Remote Ischemic Conditioning Induced Hepatoprotection in a Rodent Model of Liver Transplantation. Issue 5 (November 2019) - Emontzpohl, Christoph; Stoppe, Christian; Theißen, Alexander; Beckers, Christian; Neumann, Ulf P.; Lurje, Georg; Ju, Cynthia; Bernhagen, Jürgen; Tolba, René H.; Czigany, Zoltan
ABSTRACT: Background: Macrophage migration inhibitory factor (MIF) is an important stress-regulating mediator of acute ischemia/reperfusion (I/R) injury and ischemic conditioning. The present study aimed to investigate whether MIF is involved in the effects of remote ischemic conditioning (RIC) in a rat model of orthotopic liver transplantation (OLT). Methods: OLTs were performed in male Lewis rats (245 g–340 g). Recipients were allocated in a randomized fashion into three experimental groups: remote preconditioning-RIPC, remote post-conditioning-RIPOST, control. RIC was applied as 4×5-5 min I/R via clamping of the infrarenal aorta. Animals were followed for 1, 3, 24, 168 h post-reperfusion (n = 6 recipient/group/time point). Graft micro- and macrocirculation and hepatocellular damage were assessed. Messenger ribonucleic acid (mRNA) expression, serum, and tissue protein levels of MIF, as well as additional markers of I/R injury, were measured. Results: RIC resulted in a prominent downregulation of MIF mRNA, serum, and tissue protein. Compared with control, hepatocellular damage was significantly mitigated after RIPC or RIPOST (serum ALT; RIPC, RIPOST vs. Control, P = 0.008, P = 0.030, respectively). Graft circulation was better preserved in the RIC groups. Furthermore, there was a significant positive correlation between serum MIF and transaminase levels (r = 0.330; P = 0.02). RIC showed a significant effect on iNOS and STAT5 mRNA expressions. Supporting findings were obtained from the measurements of tissue CXCL12 mRNA expression and pAkt/Akt, pErk/Erk. Conclusion: In this sophisticated experimental model of OLT, RIC-induced hepatoprotective effects were associated with a downregulation of MIF at mRNA and protein levels, suggesting the role of MIF as a mediator in RIC-induced protection following OLT. Abstract : Supplemental Digital Content is available in the text